The rpoS gene from Yersinia enterocolitica and its influence on expression of virulence factors. - Iriarte, M (1995)
The chromosome of Yersinia enterocolitica encodes a heat-stable enterotoxin called Yst and a surface antigen called Myf, which closely resembles enterotoxin-associated fimbriae. Both factors could act in conjunction to produce diarrhea. Production of the enterotoxin is regulated by temperature, osmolarity, and pH and occurs only when bacteria reach the stationary phase. Myf production is regulated by temperature and pH and, as we show in this work, also occurs after the exponential growth phase. In an attempt to understand the late-phase expression of yst and myf, we cloned, sequenced, and mutagenized the gene encoding RpoS, an alternative sigma factor of the RNA polymerase involved in expression of stationary-phase genes in other enterobacteria. An intact rpoS gene was necessary for full expression of yst in the stationary phase but not for the expression of myf and of pYV-encoded virulence determinants.